Engineering And Durability Properties Of Fibrous Cementitious Composites Containing Hybrid, Kenaf And Barchip - Samsudin, Muhamad Fadli (2018)
Engineering and durability properties of fibrous cementitious composites containing hybrid, kenaf and barchip was the combination of the supplementary cementitious materials as cement replacement such as Pulverised Fuel Ash (PFA) and Ground Granulated Blast-Furnace Slag (GGBS) with additional of fibres content like Barchip and Kenaf fibre. Due to the problems that generally happen when cement content was higher will increase the carbon dioxide gases, environmental temperature, and high shrinkage. In addition, the combination of fibre was applied to improving the flexural behaviour of mortar as compared to the conventional mortar. The experimental research was conducted to characterise the attributes of PFA, GGBS, Barchip and Kenaf fibres; to investigate the rheological and engineering properties; to assess the durability performances of hardened mortar; and to study the flexural behaviour of fibrous cementitious composites containing hybrid, kenaf and barchip in term of compressive strength, flexural strength, toughness indices, ultrasonic pulse velocity, dynamic modulus of elasticity, impact load resistance, drying shrinkage, water absorption, intrinsic gas permeability, chloride penetration, total porosity, microstructure development, load-deflection response, load compressive strain response, impact load capacity, failure mode and crack development of panels and slabs. A total of seven mortar mixes were fabricated with PFA and GGBS used at constant cement replacement of 10% and 40% in combination with mono (2.5% of barchip or 2.5% kenaf fibre) and hybrid fibre (combination between barchip and kenaf